Analysis of Procurement and Inventory Control of Commercial Rice at Perum BULOG Regional Office Jambi - Wuri Ergaya, Tut; Wahyuni, Ira; Sri Nurchaini, Dewi; Sativa, Fendria (JALOW | Journal of Agribusiness and Local Wisdom, 2025)
This study aims to: 1) Describe the procurement process of commercial rice at Perum BULOG Jambi Regional Office, 2) Forecast the growth in commercial rice procurement using linear trend analysis, and 3) Analyze inventory control using the Economic Order Quantity (EOQ), Safety Stock (SS), Maximum Inventory (MI), and Reorder Point (ROP) methods. The results show that the commercial rice procurement at Perum BULOG Jambi involves collaboration with regional suppliers. Forecasting analysis using the linear trend method indicates a consistent increase in procurement volume. Meanwhile, EOQ analysis from 2019–2023 reveals an average optimal order quantity of 657,749 kg, with an average order frequency of 7 times per year. The average Safety Stock was 1,378,170 kg, Maximum Inventory was 2,035,919 kg, and Reorder Point was set at 1,410,676 kg. This study provides strategic recommendations for managing rice stock more efficiently to meet public demand and improve supply reliability.